Responses of two leafroller species to the photoactive dye Phloxine B - McNeill, M.R.; Goldson, S.L. (New Zealand Plant Protection, 2001)
The insecticidal properties of phloxine B were evaluated against lightbrown apple moth (LBAM) Epiphyas postvittana and green headed leafroller (GHLR) Planotortix excessana in laboratory bioassays A range of concentrations of phloxine B were added to general purpose diet and presented to larvae in Petri dishes High rates of mortality (8094) were achieved at concentrations of 0210 phloxine B with LC50 values of ca 01 and 027 for 1st instar LBAM and GHLR respectively The susceptibility of leafroller larvae to phloxine B was affected by light intensity and instar